2009
DOI: 10.1177/0269216309107003
|View full text |Cite
|
Sign up to set email alerts
|

Living with advanced chronic obstructive pulmonary disease: patients concerns regarding death and dying

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 17 publications
5
124
0
2
Order By: Relevance
“…177 l The failure of clinicians to initiate goal of care discussions with patients in hospital, a key finding from our study, was also evident in recent audits of the LCP, 16 in which two-thirds of people on the LCP had no recorded discussion of end-of-life care planning in their clinical notes. l Some (albeit limited) previous empirical work confirms our finding that not everyone prefers 'open awareness' when living with a life-limiting condition, 74,172,178 despite this being a key tenet of the philosophy informing palliative care provision. However, more research in this area is required, as reported below.…”
Section: Summary Of Findings In Relation To the Wider Literaturesupporting
confidence: 59%
See 1 more Smart Citation
“…177 l The failure of clinicians to initiate goal of care discussions with patients in hospital, a key finding from our study, was also evident in recent audits of the LCP, 16 in which two-thirds of people on the LCP had no recorded discussion of end-of-life care planning in their clinical notes. l Some (albeit limited) previous empirical work confirms our finding that not everyone prefers 'open awareness' when living with a life-limiting condition, 74,172,178 despite this being a key tenet of the philosophy informing palliative care provision. However, more research in this area is required, as reported below.…”
Section: Summary Of Findings In Relation To the Wider Literaturesupporting
confidence: 59%
“…Research is required to further explore these issues, particularly in light of evidence which suggests that some patients may be reluctant to receive information relating to a poor prognosis or 'bad news'. 74,75 A phased transition incorporating palliative care in parallel with disease-modifying treatments appears the most appropriate model for optimising transitions. This model is particularly relevant for patients with non-cancer disease, whose condition may be more slowly progressive, or with fluctuating trajectories.…”
Section: Optimising and Improving Transitionsmentioning
confidence: 99%
“…Having an opportunity to meet with healthcare staff after day surgery is important to patients (Rhodes et al, 2006, Gilmartin, 2007, Stomberg et al, 2008, Knier et al, 2015. Day surgery leads to emotional stress, such as anxiety and fear, counselling meaning that emotional counselling is also necessary (Hagberth, 2008, Stomberg et al, 2008, Gardiner et al, 2009). Prior to discharge, the content of counselling should include information about nausea, fatigue and possible urinary problems (Susilahti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The chronic diseases researched included Chronic pulmonary disease (COPD) [46,47] , asthma [48,49] , hypertension [50,51] , rheumatoid arthritis [42,43,52,53] , diabetes [40,54,[55][56][57][58] , heart failure [59][60][61] and chronic back pain [44,62] . One study encompassed several chronic diseases: diabetes, congestive heart failure and hypertension [41] .…”
Section: General Description Of Studiesmentioning
confidence: 99%
“…Table 3. Narrative synthesis of counseling needs with chronic illness with chronic illness [41,43,45,46,49,51,54,58,59,61,63,64] . Despite having counseling, many adults with chronic illness had difficulty in understanding the information and advice they received [44-46, 55, 59, 60, 61, 70] .…”
Section: The Counseling Needs Of Adults With Chronic Illnessmentioning
confidence: 99%